Anionic water-soluble polymer dispersion and method for producing same

The use of magnesium sulfate and 2-acrylic amid-2-methylpropanesulfonic acid in the production of anionic water-soluble polymer dispersions addresses synthesis challenges, reduces nitrogen content, and improves stability, achieving high molecular weight and long-term stability.

JP7623650B2Active Publication Date: 2025-01-29HYMO CORPORATION
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021023845
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-18
Publication Date
2025-01-29
Estimated Expiration
2041-02-18

AI Technical Summary

Technical Problem

Existing anionic water-soluble polymer dispersions face challenges in synthesizing hydrophobic groups, have high nitrogen content from ammonium sulfate, and suffer from poor long-term stability and separation issues.

Method used

A method for producing anionic water-soluble polymer dispersions using magnesium sulfate as an inorganic salt and 2-acrylic amid-2-methylpropanesulfonic acid or its salt as a constituent unit, avoiding ammonium sulfate, to achieve high molecular weight and improved stability.

Benefits of technology

The method results in a polymer dispersion with reduced nitrogen content, high molecular weight, and enhanced long-term stability, overcoming the limitations of ammonium sulfate-based methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623650000001
    Figure 0007623650000001
  • Figure 0007623650000002
    Figure 0007623650000002
  • Figure 0007623650000003
    Figure 0007623650000003
Patent Text Reader

Abstract

To provide an anionic water-soluble polymer dispersion having excellent product stability without using ammonium sulfate by a dispersion polymerization method under the coexistence of a polymer dispersant in an aqueous salt solution and to provide a method for producing a water-soluble polymer dispersion.SOLUTION: There can be provided an anionic water-soluble polymer dispersion having excellent product stability without using ammonium sulfate by dispersion polymerization of a monomer or a monomer mixture containing a specific monomer as essential in an aqueous salt solution containing magnesium sulfate under the coexistence of a polymer dispersant containing 2-acrylamide-2-methylpropanesulfonic acid or a salt thereof as a constitutional unit.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an anionic water-soluble polymer dispersion obtained by dispersion polymerization in an aqueous salt solution in the presence of a polymeric dispersant, and to a method for producing the same. [Background technology]

[0002] Various techniques have been reported so far, such as in Patent Document 1, regarding ionic water-soluble polymer dispersions produced by dispersion polymerization in the presence of an ionic polymer dispersant in an aqueous salt solution. Among these, anionic water-soluble polymer dispersions are widely used as flocculants for wastewater treatment and sludge dewatering, as retention aids and drainage aids for papermaking, as soil solidification agents for civil engineering, etc. For these applications, there is a particular demand for high molecular weight anionic water-soluble polymers. However, compared with cationic water-soluble polymer dispersions, it is difficult to produce stable dispersions by precipitating polymers in salt water and producing them by dispersion polymerization in general high molecular weight anionic water-soluble polymer dispersions. In the case of cationic monomers, it is easy to synthesize polymers that are insoluble in salt water by polymerizing monomers that have hydrophobic groups such as benzyl groups or long-chain alkyl groups, and the molecular weight is also sufficient for use as a flocculant. On the other hand, in the case of anionic monomers, it is difficult to introduce hydrophobic groups into the molecules, so a method of copolymerizing hydrophobic monomers is considered, but copolymerizing these hydrophobic monomers often does not result in high molecular weights. Accordingly, various reports have been made on techniques for producing anionic water-soluble polymer dispersions. For example, Patent Documents 2 and 3 disclose an anionic water-soluble polymer dispersion that is polymerized in a salt solution in the presence of an anionized water-soluble polymer stabilizer. Patent Document 4 discloses the provision of a stable dispersion of a high molecular weight sulfonic acid group-containing anionic water-soluble polymer. Patent Document 5 discloses a method for producing an anionic water-soluble polymer dispersion using a low molecular weight sulfonic acid group-containing polymer as a polymer dispersant. However, when these anionic water-soluble polymer dispersions are produced, ammonium sulfate is generally used as an inorganic salt, and the total nitrogen content derived from the ammonium sulfate salt constituting the dispersion is about 75,000 ppm (relative to the water-soluble polymer dispersion product). The total nitrogen content has a significant impact on agricultural crops. Plants absorb nitrogen in the form of ammonium nitrogen or nitrate nitrogen and use it for their growth. However, it is known that an excess of nitrogen can have a negative effect, and there is a demand for a reduction in the content. In addition, since ammonium compounds have been designated as harmful substances following the amendment of the Water Pollution Control Act in 2014, there is a demand for anionic water-soluble polymer dispersions that can reduce the amount of ammonium sulfate, particularly those with a high molecular weight and high versatility. Furthermore, when an anionic water-soluble polymer dispersion product is stored for a long period of time, solidification or separation of the product can be a problem, and there is a demand for an improvement in the separation stability of the product.

[0003] [Patent Document 1] Japanese Patent Application Publication No. 62-20511 [Patent Document 2] Special Publication No. 2001-508473 [Patent Document 3] Special Publication No. 2003-508598 [Patent Document 4] JP 2002-302521 A [Patent Document 5] JP 2004-231822 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide an anionic water-soluble polymer dispersion which is obtained by a dispersion polymerization method in the coexistence of a polymer dispersant in an aqueous salt solution, and which has excellent product stability without using ammonium sulfate, and a method for producing the same. [Means for solving the problem]

[0005] As a result of intensive research conducted to solve the above problems, it has been found that an anionic water-soluble polymer dispersion can be obtained by dispersing a monomer or a monomer mixture essentially containing a specific monomer in an aqueous salt solution containing magnesium sulfate in the presence of a polymer dispersant having 2-acrylamido-2-methylpropanesulfonic acid or a salt thereof as a constituent unit. Effect of the Invention

[0006] The dispersion in the present invention is an anionic water-soluble polymer dispersion and a production method thereof that do not use ammonium sulfate, and can suppress the nitrogen content derived from salt released into the environment, and can obtain an anionic water-soluble polymer dispersion that has a high molecular weight and excellent long-term stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The water-soluble polymer dispersion in the present invention is an anionic water-soluble polymer dispersion obtained by dispersing and polymerizing, in an aqueous salt solution, an aqueous monomer or monomer mixture solution essentially containing a monomer represented by the following general formula (1) in the presence of a polymer dispersant soluble in the aqueous salt solution under stirring: TIFF0007623650000001.tif2853 General formula (1) R1 represents hydrogen, a methyl group or a carboxymethyl group, Q represents SO3, C6H4SO3, CONHC(CH3)2CH2SO3, C6H4COO or COO, R2 represents hydrogen or COOY2, and Y1 or Y2 represents hydrogen or a cation.

[0008] The anionic monomer represented by the general formula (1) used in producing the anionic water-soluble polymer dispersion of the present invention is in the range of 1 to 100 mol %. In order to obtain the effect of the anionic group and obtain a high molecular weight, the content is preferably 5 to 80 mol %, more preferably 5 to 60 mol %. Examples of the anionic monomer include vinyl sulfonic acid, vinylbenzene sulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, methacrylic acid, acrylic acid, itaconic acid, maleic acid, phthalic acid, p-carboxystyrene acid, and the like, and their salts. Two or more of these may be used in combination. During production, the anionic monomer can be neutralized to an arbitrary degree of neutralization with an alkali substance such as an alkali metal hydroxide, e.g., sodium hydroxide, or an amine, and polymerized.

[0009] An anionic monomer represented by the general formula (1) and a nonionic monomer may be used. Examples of the nonionic monomer used when copolymerizing the anionic monomer represented by the general formula (1) and the nonionic monomer include (meth)acrylamide, N,N-dimethylacrylamide, acrylonitrile, 2-hydroxyethyl (meth)acrylate, diacetone acrylamide, N-vinylpyrrolidone, N-vinylformamide, N-vinylacetamide, and acryloylmorpholine. Two or more of these may be used in combination.

[0010] When producing the water-soluble polymer dispersion of the present invention, a cationic monomer can be used within a range that does not inhibit the effect of the anionic group.

[0011] The cationic monomer is a quaternary product of a halide of a lower alkyl group such as methyl chloride or ethyl chloride of dimethylaminoethyl (meth)acrylate or dimethylaminopropylacrylamide. For example, (meth)acryloyloxyethyl trimethylammonium chloride, (meth)acryloyloxyethyl dimethylbenzylammonium chloride, (meth)acryloylaminopropyl trimethylammonium chloride, (meth)acryloylaminopropyl dimethylbenzylammonium chloride, (meth)acryloyloxy-2-hydroxypropyl trimethylammonium chloride, etc. Two or more of these may be combined. The cationic monomer is preferably less than 10 mol%, more preferably less than 5 mol%. Also, the anionic monomer represented by the general formula (1), the cationic monomer, and the nonionic monomer may be copolymerized.

[0012] The dispersion polymerization in salt water in the present invention can be carried out by a conventional method disclosed in JP-A-62-20511, JP-A-10-212320, JP-A-2004-231822, etc. In the present invention, a monomer or monomer mixture aqueous solution essentially containing a monomer represented by general formula (1) is dispersion polymerized in a salt solution in which a polymer dispersant having 2-acrylamido-2-methylpropanesulfonic acid or a salt thereof as a constituent unit is coexistent and magnesium sulfate is used as an inorganic salt. When dispersion polymerization is performed, the addition of a polymerization retarding substance in an amount of 0.5 to 5% by mass based on the total monomers has the effect of suppressing thickening, and the polymerizable composition can be produced by adding the substance appropriately. Examples of the polymerization retarding substance include itaconic acid, maleic acid, and phthalic acid.

[0013] In the present invention, the polymer dispersant used in dispersion polymerization in salt water contains 2-acrylamido-2-methylpropanesulfonic acid or its salt as a constituent unit. Poly2-acrylamido-2-methylpropanesulfonic acid or its salt may be used, but copolymers of 2-acrylamido-2-methylpropanesulfonic acid or its salt with nonionic monomers may also be used. Examples of nonionic monomers include acrylamide, N-vinylformamide, N-vinylacetamide, N-vinylpyrrolidone, N,N-dimethylacrylamide, acrylonitrile, diacetoneacrylamide, 2-hydroxyethyl (meth)acrylate, etc., and copolymers with acrylamide are preferred. In addition, other cationic monomers, such as (meth)acryloyloxyethyltrimethylammonium chloride, may be contained in the polymer dispersant composition.

[0014] The molecular weight of the polymer dispersant is preferably not too high because it increases the viscosity of the dispersion. Therefore, it is 5,000 to 2,000,000, and preferably 50,000 to 1,000,000. The addition rate of the polymer dispersant is 1 to 20% by mass, and preferably 3 to 20% by mass, based on the monomer. It is preferably less than 5% by mass based on the dispersion. This is because the inclusion of 5% by mass or more is economically disadvantageous and may inhibit the function of the polymer.

[0015] Ammonium sulfate is generally used as an inorganic salt for dispersion polymerization in salt water. In the present invention, magnesium sulfate is used as an inorganic salt for polymerization. By using magnesium sulfate as an essential ingredient, it is possible to suppress significant thickening and produce a water-soluble polymer dispersion with a high molecular weight and excellent separation stability. An amount of magnesium sulfate is added that reaches a saturation concentration in the salt water solution at 5% by mass or more based on the total amount of the water-soluble polymer dispersion. As for magnesium sulfate, a hydrate such as the heptahydrate can be suitably used. Other salts such as sodium chloride, potassium chloride, calcium chloride, lithium chloride, sodium sulfate, sodium carbonate, and calcium carbonate may be contained, but magnesium sulfate must be 50% by mass or more of the total amount of inorganic salts during polymerization. It is preferably 70% by mass or more. The monomers are dissolved in these inorganic salt aqueous solutions, and a polymer dispersant is further added to adjust the pH to 2 to 5. After nitrogen replacement, polymerization is started with a polymerization initiator.

[0016] The present invention has discovered that by using a polymer dispersant containing magnesium sulfate as an inorganic salt during polymerization and containing 2-acrylamido-2-methylpropanesulfonic acid or a salt thereof as a constituent unit, thickening can be suppressed and a high molecular weight anionic water-soluble polymer dispersion can be stably produced.

[0017] The use of a polymer dispersant containing magnesium sulfate as an inorganic salt during polymerization and 2-acrylamido-2-methylpropanesulfonic acid or its salt as a constituent unit has the effect of suppressing thickening. There are many theoretically unknown aspects that have not yet been explained, but the phenomenon can be extrapolated as follows. That is, as polymerization proceeds in the salt solution, the concentration of the polymer produced exceeds the solubility and the polymer particles begin to precipitate, but before that, the viscosity of the polymer itself (polymerization system) also increases due to the dissolved polymer, resulting in a state in which the dissolved polymer and precipitated particles coexist. After this, the proportion of precipitated polymer increases, the viscosity of the polymer gradually decreases, and the phase changes to a dispersed state. In this coexisting state, the main role of the dispersant during the phase transition period is thought to be to improve the slip between the precipitated particles and the gel-like dissolved polymer, and to smoothly transition the phase change from the thickened state before the phase change to the dispersed state. In the early stage of polymerization, the action of 2-acrylamido-2-methylpropanesulfonic acid or its salt, which is a constituent unit of the dispersant, is involved in the phase separation of the relatively low molecular weight of the produced polymer, smoothly progressing the phase change, and in the latter half of polymerization, the action of magnesium sulfate, which has a strong salting-out power, promotes the salting-out effect with the relatively high molecular weight of the produced polymer, and it is thought that a polymer dispersion can be stably produced. These are thought to be due to a synergistic effect of the action of 2-acrylamido-2-methylpropanesulfonic acid or its salt to smooth the phase change and the action of magnesium sulfate to promote the salting-out effect.

[0018] Ammonium sulfate is generally used as an inorganic salt for the water-soluble polymer dispersion of the present invention, but the total nitrogen content derived from ammonium sulfate salt in general-purpose products is about 75,000 ppm (in the water-soluble polymer dispersion product). By eliminating the nitrogen derived from ammonium sulfate salt, the total nitrogen content can be reduced to about 20,000 ppm (in the water-soluble polymer dispersion product). The total nitrogen content has a great influence on agricultural crops. Plants absorb nitrogen in the form of ammonium nitrogen or nitrate nitrogen and use it for their growth, but it is known that excessive nitrogen has a negative effect on the contrary, and a reduction in the content is required. In addition, ammonium compounds have been designated as harmful substances following the amendment of the Water Pollution Prevention Act in 2014, and there are concerns about the impact on the environment, and the water-soluble polymer dispersion of the present invention is extremely useful because it does not use ammonium ammonium sulfate.

[0019] The polymerization concentration is 2% by mass to 25% by mass as the monomer concentration. This is because a low monomer concentration is less practical, and a high monomer concentration is more economically advantageous in terms of transportation costs, but a monomer concentration exceeding 25% by mass increases viscosity during production, making it difficult to obtain a dispersion. The monomer concentration is preferably 5% by mass to 20% by mass. The monomer may be supplied all at once at the start of polymerization, or may be supplied in appropriate portions.

[0020] The polymerization conditions are usually appropriately determined depending on the monomers and copolymerization mol% used, and the temperature is in the range of 0 to 100°C. A radical polymerization initiator is used to start the polymerization. These initiators may be either oil-soluble or water-soluble, and polymerization can be carried out using any of azo, peroxide, and redox initiators. Examples of oil-soluble azo initiators include 2,2'-azobisisobutyronitrile, 1,1'-azobis(cyclohexanecarbonitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2-methylpropionate), and 2,2'-azobis(4-methoxy-2,4-dimethyl)valeronitrile, which are dissolved in a water-miscible solvent and added.

[0021] Examples of water-soluble azo initiators include 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, 2,2'-azobis(2-amidinopropane)dihydrochloride, 4,4'-azobis(4-cyanovaleric acid), etc. Examples of redox initiators include combinations of ammonium persulfate with sodium sulfite, sodium hydrogen sulfite, trimethylamine, tetramethylethylenediamine, etc. Examples of peroxides include ammonium or potassium persulfate, hydrogen peroxide, benzoyl peroxide, lauroyl peroxide, octanoyl peroxide, succinic peroxide, t-butylperoxy-2-ethylhexanoate, etc.

[0022] The addition rate of the azo initiator or peroxide initiator is 50 to 500 ppm, preferably 70 to 200 ppm, per monomer at the start of polymerization. However, since a single addition results in a low polymerization rate, it is preferable to add it in several portions. When copolymerizing with a redox initiator, if polymerization is started under conditions of 40°C or higher, it is difficult to control the polymerization, and a sudden temperature rise or clumping of the polymerization liquid occurs, making it difficult to obtain a stable dispersion with a high degree of polymerization; therefore, 15 to 35°C is preferred. The addition rate of this initiator is 5 to 100 ppm, preferably 10 to 100 ppm per monomer at the start of polymerization. However, since the polymerization rate is low when added once, it is preferred to add it several times. The number of additions is 2 to 5 times, preferably 2 to 3 times.

[0023] In order to adjust the degree of polymerization, it is effective to use sodium formate, isopropyl alcohol, or the like in an amount of 0.1 to 5% by mass based on the monomer.

[0024] After the polymerization reaction is completed, a salt can be added to adjust the stabilization of the product. The salt to be added may be magnesium sulfate, but sodium chloride, potassium chloride, calcium chloride, lithium chloride, sodium sulfate, sodium thiosulfate, sodium carbonate, calcium carbonate, etc. may also be used. They may also be used in combination. In particular, one or more salts selected from magnesium sulfate, sodium sulfate, and sodium thiosulfate are preferred. These salts to be added are added in the range of 1 to 10% by mass based on the total amount of the water-soluble polymer dispersion.

[0025] The anionic water-soluble polymer dispersion of the present invention can be used as an agent to be added when flocculating and treating raw sludge, excess sludge, flocculated sludge, digested sludge or a mixture of these sludges from urban sewage, sewage, general industrial wastewater, or when flocculating and dehydrating them using a decanter, belt press, filter press, screw press dehydrator or the like; an oil separating agent used in an oil refining process or an oil separation process and treatment of oil-containing industrial wastewater; a papermaking agent such as a drainage improver, a retention improver or a valuable material recovery agent in a papermaking process; and in order to function for these applications, the 0.4 mass% salt solution viscosity, which is an index of the molecular weight of the water-soluble polymer dispersion of the present invention, i.e., the aqueous solution viscosity in a 4 mass% sodium chloride aqueous solution (adjusted to pH 8.5) at 0.4 mass% of the water-soluble polymer constituting the dispersion measured at 25°C, is in the range of 5 to 200 mPa s. In particular, when used as a flocculant in wastewater treatment or sludge dewatering, as a papermaking agent for retention or drainage aid, or as a civil engineering agent for soil solidification, high molecular weight anionic water-soluble polymers are often required, and in such cases, 10-60 mol% of the anionic monomer is generally used, and the aqueous solution viscosity of 0.4 mass% in a 4 mass% sodium chloride aqueous solution is preferably 20-200 mPa·s, more preferably 50-200 mPa·s, and even more preferably 80-200 mPa·s. The viscosity of the 0.4 mass% salt aqueous solution is a value measured using a B-type viscometer (such as Toki Sangyo TVB-10M) with a No. 2 rotor at 60 rpm. The intrinsic viscosity of the water-soluble polymer dispersion at 0.5% by mass measured at 25° C. in a 4% by mass aqueous sodium chloride solution (adjusted to pH 8.5) is preferably in the range of 10 to 30 dl / g.

[0026] When an anionic water-soluble polymer dispersion product is stored for a long period of time, the solidification or separation of the product may be a problem. As an index of the separation stability of the product, it can be measured by a centrifuge operation under certain conditions using a centrifuge. In the anionic water-soluble polymer dispersion of the present invention, in this measurement test, superior separation stability is obtained compared to a general-purpose product that uses ammonium sulfate as a polymerization salt, and long-term storage is possible. EXAMPLES

[0027] The anionic water-soluble polymer dispersion of the present invention and the method for producing the same will be specifically described below, but the present invention is not limited to the following examples.

[0028] (Example 1) 91.4g of demineralized water and 71.8g of magnesium sulfate heptahydrate were added to a 0.5L separable flask equipped with an anchor blade stirrer, a cooling tube, and a nitrogen inlet tube, and the mixture was dissolved uniformly under stirring. Next, 15.9g of 80% by mass acrylic acid, 2.4g of 48% by mass sodium hydroxide, 58.6g of 50% by mass acrylamide, 0.4g of sodium formate, 0.4g of itaconic acid, and 15.4g of 15% by mass sodium poly 2-acrylamido-2-methylpropanesulfonate were added to obtain a uniform solution, which was then immersed in a 33°C water bath to stabilize the temperature. Next, under a nitrogen atmosphere, 4% by mass of an aqueous solution of ammonium persulfate and 4% by mass of an aqueous solution of sodium hydrogensulfite were added as polymerization initiators at 55 ppm per monomer, and polymerization was carried out at 30°C for 10 hours under stirring. After that, 300 ppm of the above polymerization initiator was added, and polymerization was carried out for 5 hours. After the reaction was completed, 5.0 g of sodium sulfate, 38.8 g of magnesium sulfate heptahydrate, and 0.9 g of sodium thiosulfate were added to the obtained dispersion, and the mixture was stirred until no residue was left behind to obtain a water-soluble polymer dispersion. The molar composition ratio of this water-soluble polymer was acrylamide / acrylic acid = 70 / 30 mol%. The viscosity of this dispersion was 390 mPa·s, and the viscosity when the water-soluble polymer dispersion was dissolved in a 4 mass% sodium chloride aqueous solution to a concentration of 0.4 mass% was 120 mPa·s. The theoretical total nitrogen content of this water-soluble polymer dispersion was 19650 ppm (relative to the dispersion). In addition, a centrifugation operation was performed to carry out a separation stability test. This is shown in Table 1 as Example 1.

[0029] (Example 2) 65.0 g of demineralized water and 67.7 g of magnesium sulfate heptahydrate were added to a 0.5 L separable flask equipped with an anchor blade stirrer, a cooling tube, and a nitrogen inlet tube, and the mixture was dissolved uniformly under stirring. Next, 21.6 g of 80% by mass acrylic acid, 3.2 g of 48% by mass sodium hydroxide, 79.5 g of 50% by mass acrylamide, 0.4 g of sodium formate, 0.6 g of itaconic acid, and 20.9 g of 15% by mass sodium poly 2-acrylamido-2-methylpropanesulfonate were added to obtain a uniform solution, which was then immersed in a 33°C water bath to stabilize the temperature. Next, under a nitrogen atmosphere, 4% by mass of an aqueous solution of ammonium persulfate and 4% by mass of an aqueous solution of sodium hydrogensulfite were added as polymerization initiators at 55 ppm per monomer, and polymerization was carried out at 30°C for 10 hours under stirring. After that, 300 ppm of the above polymerization initiator was added, and polymerization was carried out for 5 hours. After the reaction was completed, 4.7 g of sodium sulfate, 36.5 g of magnesium sulfate heptahydrate, and 0.9 g of sodium thiosulfate were added to the obtained dispersion, and the mixture was stirred until no residue was left behind to obtain a water-soluble polymer dispersion. The molar composition ratio of this water-soluble polymer was acrylamide / acrylic acid = 70 / 30 mol%. The viscosity of this dispersion was 1050 mPa·s, and the viscosity when the water-soluble polymer dispersion was dissolved in a 4 mass% sodium chloride aqueous solution to a concentration of 0.4 mass% was 131 mPa·s. The theoretical total nitrogen content of this water-soluble polymer dispersion was 26670 ppm (relative to the dispersion). In addition, a centrifugation operation was performed to carry out a separation stability test. This is shown in Table 1 as Example 2.

[0030] (Example 3) 110.0 g of demineralized water and 75.2 g of magnesium sulfate heptahydrate were added to a 0.5 L separable flask equipped with an anchor blade stirrer, a cooling tube, and a nitrogen inlet tube, and the mixture was dissolved uniformly under stirring. Next, 7.6 g of 80% by mass acrylic acid, 0.8 g of 48% by mass sodium hydroxide, 47.9 g of 50% by mass acrylamide, 0.4 g of sodium formate, 0.3 g of itaconic acid, and 12.0 g of 15% by mass sodium poly 2-acrylamido-2-methylpropanesulfonate were added to obtain a uniform solution, which was then immersed in a 33°C water bath to stabilize the temperature. Next, under a nitrogen atmosphere, 4% by mass of an aqueous solution of ammonium persulfate and 4% by mass of an aqueous solution of sodium hydrogensulfite were added as polymerization initiators at 55 ppm per monomer, and polymerization was carried out at 30°C for 10 hours under stirring. After that, 300 ppm of the above polymerization initiator was added, and polymerization was carried out for 5 hours. After the reaction was completed, 5.3 g of sodium sulfate, 40.6 g of magnesium sulfate heptahydrate, and 0.9 g of sodium thiosulfate were added to the obtained dispersion, and the mixture was stirred until no residue was left behind, to obtain a water-soluble polymer dispersion. The molar composition ratio of this water-soluble polymer was acrylamide / acrylic acid=80 / 20 mol%. The viscosity of this dispersion was 360 mPa·s, and the viscosity when the water-soluble polymer dispersion was dissolved in a 4 mass% sodium chloride aqueous solution to a concentration of 0.4 mass% was 31.6 mPa·s. This is shown in Table 1 as Example 4. The theoretical total nitrogen content of this water-soluble polymer dispersion was 16050 ppm (relative to the dispersion). In addition, a centrifugation operation was performed, and a separation stability test was performed. This is shown in Table 1 as Example 3.

[0031] (Example 4) 90.2g of demineralized water and 71.8g of magnesium sulfate heptahydrate were added to a 0.5L separable flask equipped with an anchor blade stirrer, a cooling tube, and a nitrogen inlet tube, and dissolved uniformly under stirring. Next, 13.3g of 80% by mass acrylic acid, 2.0g of 48% by mass sodium hydroxide, 62.8g of 50% by mass acrylamide, 0.4g of sodium formate, 0.4g of itaconic acid, and 15.4g of 15% by mass sodium poly 2-acrylamido-2-methylpropanesulfonate were added to obtain a uniform solution, which was then immersed in a 33°C water bath to stabilize the temperature. Next, under a nitrogen atmosphere, 4% by mass of an aqueous solution of ammonium persulfate and 4% by mass of an aqueous solution of sodium hydrogensulfite were added as polymerization initiators at 55 ppm per monomer, and polymerization was carried out at 30°C for 10 hours under stirring. After that, 300 ppm of the above polymerization initiator was added, and polymerization was carried out for 5 hours. After the reaction was completed, 5.0 g of sodium sulfate, 38.8 g of magnesium sulfate heptahydrate, and 0.9 g of sodium thiosulfate were added to the obtained dispersion, and the mixture was stirred until no residue was left behind to obtain a water-soluble polymer dispersion. The molar composition ratio of this water-soluble polymer was acrylamide / acrylic acid = 75 / 25 mol%. The viscosity of this dispersion was 460 mPa·s, and the viscosity when the water-soluble polymer dispersion was dissolved in a 4 mass% sodium chloride aqueous solution to a concentration of 0.4 mass% was 86.3 mPa·s. The theoretical total nitrogen content of this water-soluble polymer dispersion was 21040 ppm (relative to the dispersion). In addition, a centrifugation operation was performed to carry out a separation stability test. This is shown in Table 1 as Example 4.

[0032] (Example 5) 114.3g of demineralized water and 75.2g of magnesium sulfate heptahydrate were added to a 0.5L separable flask equipped with an anchor blade stirrer, a cooling tube, and a nitrogen inlet tube, and the mixture was dissolved uniformly under stirring. Next, 15.1g of 80% by mass acrylic acid, 2.2g of 48% by mass sodium hydroxide, 35.8g of 50% by mass acrylamide, 0.4g of sodium formate, 0.3g of itaconic acid, and 10.8g of 15% by mass sodium poly 2-acrylamido-2-methylpropanesulfonate were added to obtain a uniform solution, which was then immersed in a 33°C water bath to stabilize the temperature. Next, under a nitrogen atmosphere, 4% by mass of an aqueous solution of ammonium persulfate and 4% by mass of an aqueous solution of sodium hydrogensulfite were added as polymerization initiators at 55 ppm per monomer, and polymerization was carried out at 30°C for 10 hours under stirring. After that, 300 ppm of the above polymerization initiator was added, and polymerization was carried out for 5 hours. After the reaction was completed, 5.3 g of sodium sulfate, 40.6 g of magnesium sulfate heptahydrate, and 0.9 g of sodium thiosulfate were added to the obtained dispersion, and the mixture was stirred until no residue was left behind to obtain a water-soluble polymer dispersion. The molar composition ratio of this water-soluble polymer was acrylamide / acrylic acid = 60 / 40 mol%. The viscosity of this dispersion was 183 mPa·s, and the viscosity when the water-soluble polymer dispersion was dissolved in a 4 mass% sodium chloride aqueous solution to a concentration of 0.4 mass% was 46.6 mPa·s. The theoretical total nitrogen content of this water-soluble polymer dispersion was 12060 ppm (relative to the dispersion). In addition, a centrifugation operation was performed to carry out a separation stability test. This is shown in Table 1 as Example 5.

[0033] (Example 6) 116.5g of demineralized water and 75.2g of magnesium sulfate heptahydrate were added to a 0.5L separable flask equipped with an anchor blade stirrer, a cooling tube, and a nitrogen inlet tube, and the mixture was dissolved uniformly under stirring. Next, 26.4g of 80% by mass acrylic acid, 7.8g of 48% by mass sodium hydroxide, 17.8g of 50% by mass acrylamide, 0.4g of sodium formate, 0.3g of itaconic acid, and 12.0g of 15% by mass sodium poly 2-acrylamido-2-methylpropanesulfonate were added to obtain a uniform solution, which was then immersed in a 33°C water bath to stabilize the temperature. Next, under a nitrogen atmosphere, 4% by mass of an aqueous solution of ammonium persulfate and 4% by mass of an aqueous solution of sodium hydrogensulfite were added as polymerization initiators at 55 ppm per monomer, and polymerization was carried out at 30°C for 10 hours under stirring. After that, 300 ppm of the above polymerization initiator was added, and polymerization was carried out for 5 hours. After the reaction was completed, 5.3 g of sodium sulfate and 0.8 g of sodium thiosulfate were added to the obtained dispersion, and the mixture was stirred until no residue was left behind, to obtain a water-soluble polymer dispersion. The molar composition ratio of this water-soluble polymer was acrylamide / acrylic acid = 30 / 70 mol%. The viscosity of this dispersion was 250 mPa·s, and the viscosity when the water-soluble polymer dispersion was dissolved in a 4 mass% sodium chloride aqueous solution to a concentration of 0.4 mass% was 25.3 mPa·s. The theoretical total nitrogen content of this water-soluble polymer dispersion was 7120 ppm (relative to the dispersion). In addition, a centrifugation operation was performed, and a separation stability test was performed. This is shown in Table 1 as Example 6.

[0034] (Example 7) 115.5g of demineralized water and 75.2g of magnesium sulfate heptahydrate were added to a 0.5L separable flask equipped with an anchor blade stirrer, a cooling tube, and a nitrogen inlet tube, and the mixture was dissolved uniformly under stirring. Next, 30.1g of 80% by mass acrylic acid, 8.9g of 48% by mass sodium hydroxide, 11.9g of 50% by mass acrylamide, 0.4g of sodium formate, 0.3g of itaconic acid, and 12.0g of 15% by mass sodium poly 2-acrylamido-2-methylpropanesulfonate were added to form a uniform solution, which was then immersed in a 33°C water bath to stabilize the temperature. Next, under a nitrogen atmosphere, 4% by mass of an aqueous solution of ammonium persulfate and 4% by mass of an aqueous solution of sodium hydrogensulfite were added as polymerization initiators at 55 ppm per monomer, and polymerization was carried out at 30°C for 10 hours under stirring. After that, 300 ppm of the above polymerization initiator was added, and polymerization was carried out for 5 hours. After the reaction was completed, 5.3 g of sodium sulfate and 0.8 g of sodium thiosulfate were added to the obtained dispersion, and the mixture was stirred until no residue was left behind, to obtain a water-soluble polymer dispersion. The molar composition ratio of this water-soluble polymer was acrylamide / acrylic acid = 20 / 80 mol%. The viscosity of this dispersion was 300 mPa·s, and the viscosity was 9.5 mPa·s when the water-soluble polymer dispersion was dissolved in a 4 mass% sodium chloride aqueous solution to a concentration of 0.4 mass%. The theoretical total nitrogen content of this water-soluble polymer dispersion was 4920 ppm (relative to the dispersion). In addition, a centrifugation operation was performed, and a separation stability test was performed. This is shown in Table 1 as Example 7.

[0035] (Example 8) 91.4g of demineralized water and 71.8g of magnesium sulfate heptahydrate were added to a 0.5L separable flask equipped with an anchor blade stirrer, a cooling tube, and a nitrogen inlet tube, and the mixture was dissolved uniformly under stirring. Next, 15.9g of 80% by mass acrylic acid, 2.4g of 48% by mass sodium hydroxide, 58.6g of 50% by mass acrylamide, 0.4g of sodium formate, 0.4g of itaconic acid, and 15.4g of 15% by mass acrylamide / sodium 2-acrylamido-2-methylpropanesulfonate (5 / 95 mol%) copolymer were added to obtain a uniform solution, which was then immersed in a 33°C water bath to stabilize the temperature. Next, under a nitrogen atmosphere, 4% by mass of an aqueous solution of ammonium persulfate and 4% by mass of an aqueous solution of sodium hydrogensulfite were added as polymerization initiators at 55 ppm per monomer, and polymerization was carried out at 30°C for 10 hours under stirring. After that, 300 ppm of the above polymerization initiator was added, and polymerization was carried out for 5 hours. After the reaction was completed, 5.0 g of sodium sulfate, 38.8 g of magnesium sulfate heptahydrate, and 0.9 g of sodium thiosulfate were added to the obtained dispersion, and the mixture was stirred until no residue was left behind to obtain a water-soluble polymer dispersion. The molar composition ratio of this water-soluble polymer was acrylamide / acrylic acid = 70 / 30 mol%. The viscosity of this dispersion was 180 mPa·s, and the viscosity when the water-soluble polymer dispersion was dissolved in a 4 mass% sodium chloride aqueous solution to a concentration of 0.4 mass% was 120 mPa·s. The theoretical total nitrogen content of this water-soluble polymer dispersion was 19650 ppm (relative to the dispersion). In addition, a centrifugation operation was performed to carry out a separation stability test. This is shown in Table 1 as Example 8.

[0036] Comparative Example 1: 94.1 g of demineralized water and 71.8 g of magnesium sulfate heptahydrate were added to a 0.5 L separable flask equipped with an anchor blade stirrer, a cooling tube, and a nitrogen inlet tube, and the mixture was dissolved uniformly under stirring. Next, 15.9 g of 80% by mass acrylic acid, 10.9 g of 48% by mass sodium hydroxide, 58.6 g of 50% by mass acrylamide, 0.4 g of sodium formate, 0.4 g of itaconic acid, and 12.6 g of 15% by mass polyacrylic acid were added to obtain a uniform solution, which was then immersed in a water bath at 33°C to stabilize the temperature. Next, under a nitrogen atmosphere, 4% by mass of an aqueous solution of ammonium persulfate and 4% by mass of an aqueous solution of sodium hydrogensulfite were added as polymerization initiators at 55 ppm per monomer, and polymerization was started at 30°C under stirring. During the reaction, the viscosity of the reaction solution increased, making it difficult to stir and solidifying. This is shown in Table 1 as Comparative Example 1.

[0037] (Comparative Example 2) 92.4g of demineralized water, 24.5g of 80% by mass acrylic acid, and 1.9g of 48% by mass sodium hydroxide were added to a 0.5L separable flask equipped with an anchor blade stirrer, a cooling tube, and a nitrogen inlet tube, and uniformly dissolved under stirring. Next, 90.3g of 50% by mass acrylamide, 0.4g of sodium formate, 0.7g of itaconic acid, 23.8g of 15% by mass sodium poly 2-acrylamido-2-methylpropanesulfonate, and 50.4g of ammonium sulfate were added to make a uniform solution, and the temperature was stabilized by immersing in a 33°C water bath. Next, under a nitrogen atmosphere, 4% by mass of an aqueous solution of ammonium persulfate and 4% by mass of an aqueous solution of sodium hydrogensulfite were added as polymerization initiators at 55 ppm per monomer, and polymerization was carried out at 30°C for 10 hours under stirring. After that, 300 ppm of the above polymerization initiator was added, and polymerization was carried out for 5 hours. After the reaction was completed, 13.2 g of ammonium sulfate and 0.9 g of sodium thiosulfate were added to the obtained dispersion, and the mixture was stirred until no residue was left behind, to obtain a water-soluble polymer dispersion. The molar composition ratio of this water-soluble polymer was acrylamide / acrylic acid = 70 / 30 mol%. The viscosity of this dispersion was 486 mPa·s, and the viscosity when the water-soluble polymer dispersion was dissolved in a 4 mass% sodium chloride aqueous solution to a concentration of 0.4 mass% was 134 mPa·s. The theoretical total nitrogen content of this water-soluble polymer dispersion was 74870 ppm (relative to the dispersion). In addition, a centrifugation operation was performed, and a separation stability test was performed. This is shown in Table 1 as Comparative Example 2.

[0038] (Comparative Example 3) 137.5g of demineralized water, 16.0g of 80% acrylic acid, and 2.4g of 48% sodium hydroxide were added to a 0.5L separable flask equipped with an anchor blade stirrer, a cooling tube, and a nitrogen inlet tube, and uniformly dissolved under stirring. Next, 59.0g of 50% acrylamide, 0.4g of sodium formate, 0.4g of itaconic acid, 15.5g of 15% poly 2-acrylamide-2-methylpropanesulfonic acid sodium, and 55.2g of ammonium sulfate were added to make a uniform solution, and the temperature was stabilized by immersing in a 33°C water bath. Next, under a nitrogen atmosphere, 4% ammonium persulfate aqueous solution and 4% sodium hydrogensulfite aqueous solution were added as polymerization initiators at 55 ppm per monomer, and polymerization was carried out at 30°C for 10 hours under stirring. After that, 300 ppm of the above polymerization initiator was added, and polymerization was carried out for 5 hours. After the reaction was completed, 14.5 g of ammonium sulfate and 0.9 g of sodium thiosulfate were added to the obtained dispersion, and the mixture was stirred until no residue was left behind, to obtain a water-soluble polymer dispersion. The molar composition ratio of this water-soluble polymer was acrylamide / acrylic acid = 70 / 30 mol%. The viscosity of this dispersion was 67 mPa s. The theoretical total nitrogen content of this water-soluble polymer dispersion was 68,700 ppm (relative to the dispersion). In addition, a centrifugation operation was performed, and a separation stability test was carried out. This is shown in Table 1 as Comparative Example 3.

[0039] (Comparative Example 4) 108.6g of demineralized water, 21.7g of 80% by mass acrylic acid, and 3.2g of 48% by mass sodium hydroxide were added to a 0.5L separable flask equipped with an anchor blade stirrer, a cooling tube, and a nitrogen inlet tube, and uniformly dissolved under stirring. Next, 79.9g of 50% by mass acrylamide, 0.4g of sodium formate, 0.6g of itaconic acid, 21.01g of 15% by mass sodium poly 2-acrylamido-2-methylpropanesulfonate, and 52.0g of ammonium sulfate were added to make a uniform solution, and the temperature was stabilized by immersing in a 33°C water bath. Next, under a nitrogen atmosphere, 4% by mass of ammonium persulfate aqueous solution and 4% by mass of sodium hydrogensulfite aqueous solution were added as polymerization initiators at 55 ppm per monomer, and polymerization was carried out at 30°C for 10 hours under stirring. After that, 300 ppm of the above polymerization initiator was added, and polymerization was carried out for 5 hours. After the reaction was completed, 13.6 g of ammonium sulfate and 0.9 g of sodium thiosulfate were added to the obtained dispersion, and the mixture was stirred until no residue was left behind, to obtain a water-soluble polymer dispersion. The molar composition ratio of this water-soluble polymer was acrylamide / acrylic acid = 70 / 30 mol%. The viscosity of this dispersion was 265 mPa s. The theoretical total nitrogen content of this water-soluble polymer dispersion was 72790 ppm (relative to the dispersion). In addition, a centrifugation operation was performed, and a separation stability test was carried out. This is shown in Table 1 as Comparative Example 4.

[0040] (Table 1) TIFF0007623650000002.tif4791 Monomer composition; AAM: acrylamide, AAC: acrylic acid Polymeric dispersants; p-AMPS: Poly(2-acrylamido-2-methylpropanesulfonic acid, sodium salt) AAM / AMPS: Acrylamide / sodium 2-acrylamido-2-methylpropanesulfonate (5 / 95 mol%) copolymer p-AAC: polyacrylic acid, polymer dispersant addition rate (mass%): relative to monomer Polymerization salt: a; magnesium sulfate heptahydrate, b; ammonium sulfate Monomer concentration: mass ratio of monomer to water-soluble polymer dispersion Inorganic salt concentration: mass ratio of inorganic salt to water-soluble polymer dispersion Dispersion viscosity: Viscosity of water-soluble polymer dispersion measured at 25°C Viscosity of 0.4% by mass salt water solution: Viscosity (pH 8.5) measured at 25°C when dissolved in 4% by mass sodium chloride water to give a polymer concentration of 0.4% by mass. Intrinsic viscosity: Intrinsic viscosity of 0.5% by mass of a water-soluble polymer dispersion measured at 25°C in a 4% by mass saline solution (pH 8.5) Centrifugation supernatant: 40 g of the dispersion was collected in a centrifuge tube and centrifuged at 4,000 rpm for 10 minutes. The height of the supernatant was then measured and its ratio to the height of the dispersion was calculated. Centrifugation residue: 40 g of the dispersion was placed in a centrifuge tube and centrifuged at 4,000 rpm for 10 minutes. The centrifuge tube was then turned upside down for 120 seconds to measure the amount of precipitated residue, and the mass percentage relative to the dispersion was calculated.

[0041] In Examples 1 to 8 of anionic water-soluble polymer dispersions obtained by using magnesium sulfate as an inorganic salt during polymerization and a polymer having 2-acrylamido-2-methylpropanesulfonic acid or its salt as a constituent unit as a dispersant, water-soluble polymer dispersions were obtained without using ammonium sulfate during polymerization. Moreover, compared with the comparative example of a general-purpose product using ammonium sulfate as an inorganic salt during polymerization, the amount of centrifugal supernatant and centrifugal residue in the separation stability test was small, and it was found that the product stability was good. On the other hand, in Comparative Example 1, in which magnesium sulfate was used as the inorganic salt during polymerization but a polymer dispersant not containing 2-acrylamido-2-methylpropanesulfonic acid or a salt thereof as a constituent unit was used, the dispersion thickened and solidified, and no dispersion was obtained. It was found that by using magnesium sulfate as the inorganic salt during polymerization and a polymer containing 2-acrylamido-2-methylpropanesulfonic acid or a salt thereof as a constituent unit as a dispersant, thickening can be suppressed without using ammonium sulfate, and an anionic water-soluble polymer dispersion with good product stability can be obtained.

Claims

1. An anionic water-soluble polymer dispersion obtained by dispersing and polymerizing, under stirring, an aqueous salt solution containing 70% by mass or more of magnesium sulfate out of the total amount of inorganic salts during polymerization, a monomer or monomer mixture aqueous solution essentially containing a monomer represented by the following general formula (1), in the presence of a polymer dispersant having 2-acrylamido-2-methylpropanesulfonic acid or a salt thereof as a constituent unit: General formula (1) R 1 is hydrogen, a methyl group or a carboxymethyl group, and Q is SO 3 , C 6 H 4 SO 3 , CONHC (CH 3 ) 2 CH 2 SO 3 , C 6 H 4 COO or COO, R 2 is hydrogen or COOY 2 , Y 1 Or Y 2 represents a hydrogen atom or a cation.

2. The anionic water-soluble polymer dispersion according to claim 1, characterized in that the viscosity of a 4 mass% aqueous sodium chloride solution at 0.4 mass% of the anionic water-soluble polymer measured at 25°C is in the range of 20 to 200 mPa·s.

3. A method for producing an anionic water-soluble polymer dispersion, characterized in that the anionic water-soluble polymer dispersion is obtained by dispersing and polymerizing, under stirring, an aqueous solution of a monomer or monomer mixture essentially containing a monomer represented by the following general formula (1) in a salt solution containing 70 mass% or more of magnesium sulfate in the total amount of inorganic salts during polymerization, in the presence of a polymer dispersant having 2-acrylamido-2-methylpropanesulfonic acid or a salt thereof as a constituent unit: General formula (1) R 1 is hydrogen, a methyl group or a carboxymethyl group, and Q is SO 3 , C 6 H 4 SO 3 , CONHC (CH 3 ) 2 CH 2 SO 3 , C 6 H 4 COO or COO, R 2 is hydrogen or COOY 2 , Y 1 Or Y 2 represents a hydrogen atom or a cation.

Citation Information

Patent Citations

  • Production of water-soluble polymer dispersion

    JP1987020511A

  • Water-soluble polymer dispersion of low inorganic salt content and method for producing the same

    JP2016003255A

  • Manufacturing method of polymer coagulant

    JP2016093800A

  • Wastewater treatment method by water-soluble polymer dispersion liquid

    JP2017159193A